2014
DOI: 10.1159/000358708
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of <b><i>ADAM17</i></b> Polymorphisms and Susceptibility to Sporadic Abdominal Aortic Aneurysm

Abstract: Background: Accumulating evidence suggests that the principal TNF-α converting enzyme, a disintegrin and metalloproteinase 17 (ADAM17), is involved in the development of human abdominal aortic aneurysm (AAA). However, the association between ADAM17 gene polymorphisms and AAA has not been explored. The present study was aimed to determine the association between ADAM17 promoter polymorphisms and AAA. Methods: A total of 316 patients with AAA and 306 age-matched healthy controls were enrolled in this study. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Many genetic researches demonstrated that several functional single nucleotide polymorphisms (SNPs) within the ADAM17 gene are associated with differences in immune inflammatory response and disease outcomes [25][26][27][28][29][30][31]. To the best of our knowledge, this present study was the first to analyze the clinical relevance of the five polymorphisms (rs55790676, rs12692386, rs11684747, rs1524668 and rs11689958) within the promoter region of ADAM17 to the susceptibility and progression of sepsis.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Many genetic researches demonstrated that several functional single nucleotide polymorphisms (SNPs) within the ADAM17 gene are associated with differences in immune inflammatory response and disease outcomes [25][26][27][28][29][30][31]. To the best of our knowledge, this present study was the first to analyze the clinical relevance of the five polymorphisms (rs55790676, rs12692386, rs11684747, rs1524668 and rs11689958) within the promoter region of ADAM17 to the susceptibility and progression of sepsis.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study has revealed that the rs11684747 polymorphism has a potential allele-specific binding site for the hepatocyte nuclear factor-1 alpha (HNF1A/B) transcription factor, which is associated with the insulin sensitivity and progression of diabetes [26,39]. Our previous studies have shown that the ADAM17 rs1524668 A>C increases the susceptibility to PACI-type stroke and that the rs12692386 GA/GG genotypes of ADAM17 are linked to high ADAM17 mRNA expression and increase susceptibility to human abdominal aortic aneurysm [28,31]. We speculate that transcriptional enhancers and other regulatory elements in the promoter regions may play various regulatory roles in the gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primers used in the SNaPshot were as follows: rs17576F: ACGTTGGATGTGGGGGTTATAATGTGCTGT, rs17576R: ACGTTGGATGTGGAAGTGAATGGAAACTG, rs3787268F: ACGTTGGATGATCCTGGGCCATAGAGGATG, rs3787268R: ACGTTGGATGTCCTCACTCAGCCTCCCTT, rs3918241F: ACGTTGGATGTCGTGACTGCAAAGCAGATG, rs3918241R: ACGTTGGATGAATGAGACTGTGAGATGGAG; rs3918242F: ACGTTGGATGCCTCCCGAGTAGCTGGTATT, rs3918242R: ACGTTGGATGCCTGGTCAACGTAGTGAAAC. The SNaPshot reactions and PCR procedures were performed as previously described [25].…”
Section: Genotypingmentioning
confidence: 99%